CASE OF TORPEDO MACULOPATHY WITH TWO DISTINCT ZONES OF THE RETINAL PIGMENT EPITHELIUM. Issue Volume 16:Issues 3(2022) (7th February 2020) - Brill, Daniel A.; Lin, Xihui; Garcia, Armando L.; Hou, Andrew C.; Le, Kim H.
Abstract : Torpedo maculopathy is a rare congenital disease of the retinal pigment epithelium. Here, we describe a unique case of torpedo maculopathy with two distinct zones of the retinal pigment epithelium visualized on optical coherence tomography, which may reveal different stages of how the disease evolves over time. Abstract : Background/Purpose: To report a case of torpedo maculopathy with two distinct zones of the retinal pigment epithelium visualized on optical coherence tomography. Methods: Observational case report. Results: A 6-year-old female presented for a routine examination. Visual acuity was 20/20 bilaterally. Dilated fundus examination was normal in the right eye. Dilated fundus examination of the left eye showed a wedge-shaped area of hypopigmentation in the temporal macula. Optical coherence tomography macula of the left eye showed outer retinal cavitation with segmentation of the foveal retinal pigment epithelium into a superficial fluffy zone and a deeper hyperreflective zone. Conclusion: This case helps contribute to the growing body of the torpedo maculopathy literature that may reveal different stages of the same disease evolving over time.